Evaluation of a special parallel-plate ionization chamber in standard mammography beams - Soares, Climério S.; Caldas, Linda V.E. (Applied radiation and isotopes, 2025)
The aim of this work was to verify the possibility of the application of a special parallel-plate ionization chamber, developed at the Calibration Laboratory (IPEN), for mammography dosimetry. The homemade chamber has a polymethyl methacrylate body, 10 cm of sensitive length, and a sensitive volume of 3.2 cm3. Its entrance window is a foil of Mylar and its collecting electrode is made of graphite. Some quality control and characterization tests were applied to evaluate the ionization chamber: short- and medium-term stabilities, leakage current, saturation, ion collection efficiency, polarity effect, stabilization time, linearity of response, angular dependence, and energy dependence. The tests were carried out using mammography standard radiation beams and a90Sr + 90Y check source. All the results obtained were within the international recommended limits. •A special parallel-plate ionization chamber was evaluated in mammography X-ray beams.•The ionization chamber presented excellent performance in all characterization tests.•The homemade ionization chamber was built using low-cost materials.•This chamber may be used in quality control programs in laboratories and hospitals.